2020
DOI: 10.3390/molecules25122832
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal Activity of Thymbra capitata (L.) Cav. Essential Oil

Abstract: The bioherbicidal potential of Thymbra capitata (L.) Cav. essential oil (EO) and its main compound carvacrol was investigated. In in vitro assays, the EO blocked the germination and seedling growth of Erigeron canadensis L., Sonchus oleraceus (L.) L., and Chenopodium album L. at 0.125 µL/mL, of Setaria verticillata (L.) P.Beauv., Avena fatua L., and Solanum nigrum L. at 0.5 µL/mL, of Amaranthus retroflexus L. at 1 µL/mL and of Portulaca oleracea L., and Echinochloa crus-galli (L.) P.Beauv. at 2 µL/mL. Under gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 77 publications
(87 reference statements)
1
11
1
Order By: Relevance
“…Regarding the latter issue, it is important to highlight that tested EOs could be an important and sustainable tool for weed management, not only by killing target weeds but also reducing their ability to compete with the crops, as they were capable to reduce their vigor and growth. Many in vitro studies have shown that T. capitata EO was able to inhibit seed germination of several noxious weeds [ 15 , 35 , 36 , 62 , 63 ], such as Erigeron bonariensis , one of the most important cosmopolite weeds especially in no-tilled soils with problems of resistance to glyphosate [ 15 , 35 , 46 ]. In addition, T. capitata has been described as an allelopathic species capable of reducing both germination and growth of neighboring species [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the latter issue, it is important to highlight that tested EOs could be an important and sustainable tool for weed management, not only by killing target weeds but also reducing their ability to compete with the crops, as they were capable to reduce their vigor and growth. Many in vitro studies have shown that T. capitata EO was able to inhibit seed germination of several noxious weeds [ 15 , 35 , 36 , 62 , 63 ], such as Erigeron bonariensis , one of the most important cosmopolite weeds especially in no-tilled soils with problems of resistance to glyphosate [ 15 , 35 , 46 ]. In addition, T. capitata has been described as an allelopathic species capable of reducing both germination and growth of neighboring species [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…A. fatua seeds were germinated using 8 h (23.0 ± 0.1 °C)/16 h (18.0 ± 0.1 °C) light/dark conditions. Germination conditions were established based in previous works [ 36 ]. After germination (about 1 week), emerged seedlings were selected for uniformity in growth and individually transplanted in polypropylene square pots (8 × 8 × 7 cm) previously filled with a 2 cm drainage layer of perlite and a 5 cm layer of soil (220 g) collected in an organic citrus orchard (39°37′24.8″ N, 0°17′25.6″ W, Puzol, Valencia, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…T. capita was the most effective EO, killing all weeds at the highest dose applied (12 µL/mL), except P. oleracea , which was eliminated in 90%. As T. capitata EO demonstrated the highest herbicidal potential, it was studied more in detail, through in vitro and in vivo experiments carried out on many weeds [ 72 ] ( Table 1 ). In vitro experiments showed the strong herbicidal potential of T. capitata EO, which controlled completely the germination of different common and problematic weed species, although they showed different sensitivity to the EO, as it blocked the germination and seedling development of E. canadensis , Sonchus oleraceus (L.) L. and C. album at 0.125 μL/mL (more sensitive species), of Setaria verticillata (L.) P.…”
Section: Herbicidal Activity Of Essential Oilsmentioning
confidence: 99%
“…With the objective to determine which mode of application was more effective, spraying or watering, T. capitata EO was applied on A. fatua by spraying and by irrigation. Comparing the data obtained in A. fatua and in other species, it was concluded that T. capitata EO was more effective at the same doses applied by irrigation in monocotyledons and by spraying in dicotyledons [ 72 ].…”
Section: Herbicidal Activity Of Essential Oilsmentioning
confidence: 99%